Lipids and lipoproteins in Friedreich's ataxia. Issue 2 (February 1980) - Walker, J L; Chamberlain, S; Robinson, N
Abstract : Friedreich's ataxia is an autosomal recessively inherited disease affecting the nervous system with a high incidence of heart involvement. Abnormalities of lipid metabolism are known to be associated with several progressive ataxic conditions. In this study of 46 Friedreich's ataxia patients, serum lipids, fatty acids and lipoproteins were assayed and compared with some earlier findings on Friedreich's ataxia and related disorders. Abnormalities of low and high density lipoproteins suggestive of a major defect have been reported; in the present study the level and chemical composition of high density lipoprotein has been assessed in 20 Friedreich's ataxia patients but previous abnormalities could not be substantiated. Lipid compositional analysis of Friedreich's ataxia central nervous tissue and heart, which has not been previously reported, did not markedly differ from control tissue.